Graceful Exits. - Campbell, Debra, 1953- (Indiana University Press, 2003)
The personal narratives of nine 20th-century writers speak eloquently about the process of departure from the Catholic church and its institutions. Debra Campbell explores each author's breaking of the taboo associated with women leaving their "proper place." She locates five themes at the heart of all their narratives: reversals, boundary crossings, diaspora, renaming, and recycling. Campbell examines how each women grapples with the spirituality of departure and shows that the very process of leaving Catholic institutions is a Catholic enterprise.